Analisis Harga Saham Ditinjau dari Rasio Keuangan Perusahaan yang Listing di Jakarta Islamic Index (JII) Periode 2015-2017 - Cahya, Bayu Tri; Vitriani, Eri; Andriani, Asih (AKTSAR: Jurnal Akuntansi Syariah, 2019)
This study aims to determine the Return on Asset (ROA), Current Ratio (CR), Debt to Equity Ratio (DER), Inventory Turn Over (ITO) on stock price in companies registered in the Jakarta Islamic Index in 2015-2017. The approach used in this study is a quantitative approach. The data in this study are secondary data. The data obtained from the site www.idx.go.id and the website of each company. The sample determination technique uses purposive sampling technique and data analysis using multiple regression analysis. The findings show that Return on Asset (ROA) affect stock price while Current Ratio (CR), Debt to Equity Ratio (DER), dan Inventory Turn Over (ITO) have no effect on the stock price.